Effect of Menstrugole on primary dysmenorrhea: a randomized clinical trial - Fatemeh Shobeiri; Sasan Nazari; Saman Nazari; Ensiyeh Jenabi; Arezoo Shayan (Korean Society of Obstetrics and Gynecology, 2018)
ObjectivePrimary dysmenorrhea occurs in more than 50% of women of reproductive age. This survey evaluated the effects of Menstrugole on the alleviation of primary dysmenorrhea.MethodsThis study was performed in western Iran between August 15 and December 15, 2017, in female students with primary dysmenorrhea. The students were randomly divided into 2 groups and received placebo or a Menstrugole capsule for 3 days in each of 2 menstrual cycles. The visual analog scale was used to assess pain severity. The χ2 test, one-way analysis of variance, and the paired t-test were used for statistical evaluation.ResultsWe compared the severity of pain between the 2 groups. There was a significant change in the mean pain score during the first (P<0.001) and second months (P<0.001) after the use of Menstrugole, compared with that in the placebo group.ConclusionMenstrugole decreased pain severity in female students, and can be considered by health care providers for treatment of primary dysmenorrhea.